2021
DOI: 10.3389/fgene.2021.700489
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Milk Somatic Cells During Lactation Between Two Intensively Reared Dairy Sheep Breeds

Abstract: In dairy sheep industry, milk production dictates the value of a ewe. Milk production is directly related to the morphology and physiology of the mammary gland; both being designated targets of breeding strategies. Although within a flock breeding parameters are mutual, large differences in milk production among individual ewes are usually observed. In this work, we tested two of the most productive dairy sheep breeds reared intensively in Greece, one local the Chios breed and one foreign the Lacaune breed. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…EPPK1 plays a role in the production of unsaturated fatty acids (Bohlouli et al., 2022). GPSM2 plays an important role in mammary gland productivity in high‐yielding animals (Michailidou et al., 2021). PLEC has been identified as a candidate gene associated with milk, fat, and protein yield, and fat and protein percentage in Holstein cattle (Cai et al., 2020; Jiang, Ma, et al., 2019; Pedrosa et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPPK1 plays a role in the production of unsaturated fatty acids (Bohlouli et al., 2022). GPSM2 plays an important role in mammary gland productivity in high‐yielding animals (Michailidou et al., 2021). PLEC has been identified as a candidate gene associated with milk, fat, and protein yield, and fat and protein percentage in Holstein cattle (Cai et al., 2020; Jiang, Ma, et al., 2019; Pedrosa et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…DGAT1 encodes an enzyme with an important metabolic role that can convert diacylglycerol and fatty acyl CoA into triacylglycerol. The MGST1 gene plays a role in hydrophobic metabolism, (Morgenstern et al, 2011). This is one of the candidate genes for the milk production trait (Iung et al, 2019;Pedrosa et al, 2021).…”
Section: Sc Sionmentioning
confidence: 99%
“…From domestication to the current pattern of differentiation, domestic species have been influenced by lots of factors such as migration, isolation, and introgression; these have resulted in a very large number of sheep breeds across the world [2]. A large quantity of dairy sheep are distributed in Mediterranean and Black Sea regions, so the sheep milk industry is mainly concentrated in parts of Europe, West Asia, and African countries such as France, Greece, Italy, Spain, Israel, Turkey, and so on; some dairy sheep breeds like the East Friesian sheep, Sarda sheep, Lacaune sheep, Latxa sheep, and Assaf sheep are all high producing sheep breeds known to the world [3]. Previous reports showed that sheep milk has higher fat content, protein content, lactose content, ash content, and total non-fat solids, which have higher nutritional value and can be processed into various delicious milk products and by-products.…”
Section: Introductionmentioning
confidence: 99%